Understanding the role of Oryza sativa OsPILS (PIN Like) genes in auxin signaling - Mohanta, Tapan Kumar; Mohanta, Nibedita (PeerJ PrePrints, 2014)
The phytohormone auxin is one of the most important signaling molecule that undergo accumulation or depletion in temporal or spatial manner due to wide arrays of changes in developmental or stress programme. Proper distribution, maintenance and homeostasis of auxin molecules across the plant system is one of the most important phenomena. The distribution and homeostasis of auxin is maintained by auxin transport system across the plant. Auxin transportation is carried out by auxin transporter family proteins, popularly known as auxin efflux carriers (PINs). Besides, auxin efflux carrier family proteins, a sub-family of auxin efflux carriers (OsPILS) being identified from Oryza sativa and reported here. Oryza sativa encodes for seven putative sub-cellularly localized transmembrane PILS proteins. Differential expression of OsPILS genes are found to be regulated by auxin and cytokinin dependent manner. In auxin treated plants, all OsPILS genes are up-regulated in leaf tissues and down regulated in root tissues during third week time point. In cytokinin treated plants, maximum of OsPILS genes were up-regulated both in leafs and roots tissues during third week time period. Regulation of gene expression of OsPILS genes by auxin and cytokinin during third week time period reflects its important roles during plant growth and development.
Keywords: AtPIN; OsPIN; OsPILS; AtPILS